Symphony armchair / Mohamad Muizzuddin Mohamad Nurul Azmi - Mohamad Nurul Azmi, Mohamad Muizzuddin (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2024)
"Symphony: Nature's Armchair Crab in Your Living Room" This final portfolio project explores the exciting world of furniture design, where the spotlight is on an unexpected yet fascinating subject – crabs. We're taking a close look at how crabs move and translating that awesomeness into comfy armchairs for your living room. Think of it like giving your furniture some cool dance moves! The armchairs will have special features that work a bit like crab joints, making them not just comfy but also unique and fun. To conclude, "Symphony" is about making your living room special. It's not just about having a comfy seat; it's about having a piece of furniture that's inspired by nature and looks super cool. Join us in this adventure as we blend the natural world with modern living, creating a "Symphony" that brings joy to your space.